THE IMPACT OF THE EU ON AGENCIFICATION AND DEPOLITICISATION IN LITHUANIA - Nakrošis, Vitalis; Bankauskaitė-Grigaliūnienė, Sabina (Baltic Journal of Political Science, 2015)
This article compares the actual patterns of agencification and depoliticisation in Lithuania and explains the extent to which the EU influenced these changes. Our research employs (descriptive and inferential) statistical analysis of data on the organisational changes of Lithuanian agencies and the political participation of their managers in the 1990-2012 period. The article found that the EU made a significant contribution to the establishment of new agencies but changes in the scope of politicisation can be explained by a combination of evolution in the political conditionality of EU membership and wholesale government changes. The differentiated impact of the EU on public administration changes was observed with the management of the Europeanised agencies becoming increasingly professional over time. Overall, the results of our research confirm the stronger and more enduring impact of specific acquis rules in the policy domain compared to the much weaker influence of the EU’s political conditionality.